Offsetting versus Mitigation Activities to Reduce CO2 Emissions: A Theoretical and Empirical Analysis for the U.S. and Germany - Andreas Lange; Andreas Ziegler (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
This paper studies the voluntary provision of public goods that is partially driven by a desire to offset for individual polluting activities. We first extend existing theory and show that offsets allow a reduction in effective environmental pollution levels while not necessarily extending the consumption of a polluting good. We further show a nonmonotonic income-pollution relationship and derive comparative static results for the impact of an increasing environmental preference on purchases of offsets and mitigation activities. Several theoretical results are then econometrically tested using a novel data set on activities to reduce CO2 emissions for the case of vehicle purchases in the U.S. and Germany. We show that an increased environmental preference triggers the use of CO2 offsetting and mitigation channels in both countries. However, we find strong country differences for the purchase of CO2 offsets. While such activities are already triggered by a high general awareness of the climate change problem in the U.S., driver's license holders in Germany need to additionally perceive road traffic as being responsible for CO2 emissions to a large extent.
Keywords: C25; C35; H41; Q54; 330; public good; voluntary provision; climate change; CO2 offsetting; vehicle purchase; discrete choice models; Klimaschutz; Treibhausgas-Emissionen; Luftreinhaltung; Umweltbewusstsein; Straßenverkehr; Nachhaltige Mobilität; Wahrnehmung; Vergleich; USA; Deutschland